An analytical model describing the in-plane behaviour of timber diaphragms strengthened with plywood panels. (15th May 2021) - Mirra, Michele; Ravenshorst, Geert; de Vries, Peter; van de Kuilen, Jan-Willem
Highlights: Load-slip response of a plank-plywood panel screw is modelled with a novel equation. In-plane response of timber floors retrofitted with plywood panels is predicted from the screws one. The analytical model accurately predicts strength, stiffness and energy dissipation of the floors. The model enables a more precise design and characterization of timber floors retrofitted with plywood panels. Abstract: Timber diaphragms in existing buildings are often too flexible in their plane, and can thus potentially cause out-of-plane collapses of walls during earthquakes. A very efficient retrofitting method to increase their in-plane stiffness and energy dissipation is the overlay of plywood panels. However, the usual characterization of the floors by means of a general equivalent shear stiffness cannot account for their nonlinearity and dissipative properties. Therefore, in this work, an analytical model is formulated to describe the in-plane response of timber diaphragms strengthened with plywood panels screwed along their perimeter to the existing sheathing. The proposed formulation starts from the definition of the load-slip equation for a single screw connecting a plank and a plywood panel. The whole floor's response is then derived, with the prediction of both backbone curve and pinching cycles. From the comparison between the response of tested full-scale diaphragms and the analytically calculated one, it can be concluded that the proposed model accurately predicts the in-plane behaviour and dissipative properties of timber floors retrofitted with plywood panels.